The fight for the city: controversies in the formulation process of the Cusco Plan to 2025 – Mobility and Public Space in a World Heritage City (Cusco 2014-2018) - Concha Vásquez, Claudia Alejandra (2018)
Through coordination between the Regional Government of Cusco, UNESCO and the World Bank, the Plan for Mobility and Public Space Cusco 2025 was born. This plan aimed to order the vehicular system of the city, generate neighborhoods where the population can occupy the public space enjoying the streets, parks and squares, and implement a new urban transport model consisting of a main route with intelligent traffic lights. The process of formulating this plan has been surrounded by technical, political and coordination conflicts between the different institutions involved. Additionally, it came into conflict with the city models and the interests of different local actors, such as the residents of the city center, the tourism companies, among others.This paper aims to identify the factors that hindered the development of the Cusco Plan by 2025, placing special emphasis on the definitions of the public problem, the technical and political capacities of the institutions involved as well as the response from the press and the citizens of Cusco. This, in turn, will allow us to delve into the study of the paradox of those initiatives which are planned and have political and economic support from local and international institutions, but still encounter difficulties throughout their development, which finally leads to partial implementation or the cancellation of the policy.